2006
DOI: 10.1074/jbc.m605677200
|View full text |Cite
|
Sign up to set email alerts
|

Allelic Gene Regulation of Pcdh-α and Pcdh-γ Clusters Involving Both Monoallelic and Biallelic Expression in Single Purkinje Cells

Abstract: The molecular basis for providing the identity and diversity of single neurons is a key for realizing the brain system. Diverse protocadherin isoforms encoded by the Pcdh-␣ and Pcdh-␥ gene clusters are expressed in all of the vertebrates studied. For the Pcdh-␣ isoforms, differential expression patterns have been found in single Purkinje cells by unusual monoallelic and combinatorial types of gene regulation. Here we investigated total allelic gene regulation in the Pcdh-␣ and -␥ clusters, including the C-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
226
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(239 citation statements)
references
References 37 publications
12
226
1
Order By: Relevance
“…1 D and E). This relatively simple pattern of expression is reminiscent of that observed with individual Purkinje cells, which express a small subset of alternate isoforms and the ubiquitous isoforms (6,7). It appears that the promoter choice made in this clonal line is epigenetically stable, because the same pattern of active isoforms is consistently observed.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…1 D and E). This relatively simple pattern of expression is reminiscent of that observed with individual Purkinje cells, which express a small subset of alternate isoforms and the ubiquitous isoforms (6,7). It appears that the promoter choice made in this clonal line is epigenetically stable, because the same pattern of active isoforms is consistently observed.…”
Section: Resultsmentioning
confidence: 70%
“…However, we find that the human neuroblastoma cell line SK-N-SH is diploid (Fig. S1) (12) and that the pattern of Pcdh expression is what would be expected from a single neuron (6,7).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, αc1 is expressed from both chromosomes in all neurons (5). The lower level of Rad21 binding at alternative isoforms is consistent with stochastic expression of these isoforms generating heterogeneity within the population of cells assayed, resulting in a reduced ChIP signal.…”
Section: Binding Of Rad21 To the Pcdhα Cse Correlates With Expressionmentioning
confidence: 74%
“…Over 50 clustered Pcdh genes are organized into three contiguous gene clusters: Pcdhα, Pcdhβ, and Pcdhγ. Single-cell analysis of Pcdhα and -γ gene expression in mouse Purkinje neurons revealed that "alternative" Pcdhα and -γ isoforms are stochastically expressed from each of the two chromosomes, whereas the five "c-type" isoforms are expressed biallelically in every cell (4,5). This pattern of expression could generate over 14,000 different combinations of alternative isoforms, comparable to that of the Drosophila Dscam gene.…”
mentioning
confidence: 99%
“…There are >50 distinct Pcdh isoforms encoded by three closely linked gene clusters named Pcdhα, Pcdhβ, and Pcdhγ (2). Individual neurons stochastically express distinct combinations of Pcdh isoforms, thus generating enormous cell surface diversity that may contribute to the specificity of synaptic interactions (3,4).…”
mentioning
confidence: 99%